A Novel, High-sensitivity, Bacteriophage-based Assay Identifies Low-level Mycobacterium tuberculosis Bacteremia in Immunocompetent Patients With Active and Incipient Tuberculosis. (22nd June 2019) - Verma, Raman; Swift, Benjamin M C; Handley-Hartill, Wade; Lee, Joanne K; Woltmann, Gerrit; Rees, Catherine E D; Haldar, Pranabashis
Abstract: The haematogenous dissemination of Mycobacterium tuberculosis (Mtb) is critical to the pathogenesis of progressive tuberculous infections in animal models. Using a novel, phage-based blood assay, we report the first concordant evidence in well-characterized, immunocompetent human cohorts, demonstrating associations of Mtb bacteremia with progressive phenotypes of latent infection and active pulmonary tuberculosis.